A business case for democracy: regime type, growth, and growth volatility. Issue 8 (17th November 2021) - Knutsen, Carl Henrik
ABSTRACT: I present a business case for democracy, focusing on the impact of democracy on economic growth. This relationship is widely studied, and results have been less robust for growth than many other development outcomes such as literacy or infant mortality. I discuss four factors pertaining to data quality and modelling choices, suggesting that several previous studies have underestimated the growth-benefits of democracy. I further discuss the relationships between democracy and economic crises and variation in economic performance. By mitigating abysmal economic outcomes and ensuring more stable performance, democracy is generally of benefit to risk-averse entrepreneurs, investors, workers, and consumers alike.